2017
DOI: 10.1155/2017/2945803
|View full text |Cite
|
Sign up to set email alerts
|

Dahuang Zexie Decoction Protects against High‐Fat Diet‐Induced NAFLD by Modulating Gut Microbiota‐Mediated Toll‐Like Receptor 4 Signaling Activation and Loss of Intestinal Barrier

Abstract: Increasing evidence suggests that intestinal dysbiosis, intestinal barrier dysfunction, and activated Toll-like receptor 4 (TLR4) signaling play key roles in the pathogenesis of NAFLD. Dahuang Zexie Decoction (DZD) has been verified to be effective for treating NAFLD, but the mechanisms remain unclear. In this study, we investigated the effects of DZD on NAFLD rats and determined whether such effects were associated with change of the gut microbiota, downregulated activity of the TLR4 signaling pathway, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…We previously showed that TLR4‐mediated signaling in intestinal epithelial cells regulated hepatic fibrogenesis in porcine serum‐treated diabetic rats . Activation of TLR4 in the intestine induces intestinal mucosal inflammation by mediating ERK and c‐Jun NH2‐terminal kinase phosphorylations in high‐fat diet‐fed Sprague–Dawley rats . Moreover, OCA reduces bacterial translocation along with intestinal mucosal TLR4 signaling and inhibits intestinal inflammation in a CCl4‐induced hepatic cirrhosis rat model .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We previously showed that TLR4‐mediated signaling in intestinal epithelial cells regulated hepatic fibrogenesis in porcine serum‐treated diabetic rats . Activation of TLR4 in the intestine induces intestinal mucosal inflammation by mediating ERK and c‐Jun NH2‐terminal kinase phosphorylations in high‐fat diet‐fed Sprague–Dawley rats . Moreover, OCA reduces bacterial translocation along with intestinal mucosal TLR4 signaling and inhibits intestinal inflammation in a CCl4‐induced hepatic cirrhosis rat model .…”
Section: Discussionmentioning
confidence: 97%
“…33 Activation of TLR4 in the intestine induces intestinal mucosal inflammation by mediating ERK and c-Jun NH2-terminal kinase phosphorylations in high-fat diet-fed Sprague-Dawley rats. 35 Moreover, OCA reduces bacterial translocation along with intestinal mucosal TLR4 signaling and inhibits intestinal inflammation in a CCl4-induced hepatic cirrhosis rat model. 11 The reason for the difference in the role of intestinal TLR4 signaling between these models remains indiscernible but could be related to the fact that intestinal epithelial cell expression of TLR4 differs among strains and species.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ROS may be considered as a therapeutic target in the progression of oral cancer. Dahuang, the roots of Rheum palmatum , a well-known traditional Chinese herb used for chronic kidney disease and liver disease [ 9 , 10 ]. Chrysophanol, an anthraquinone derivative isolated from the rhizomes of Rheum palmatum, has been reported to inhibit proliferation and induces apoptosis through the NF- κ B/cyclin D1 and NF- κ B/Bcl-2 signaling cascade in breast cancer cell lines [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dahuang, the root of Rheum palmatum L., is a wellknown traditional Chinese herbal medicine that has been used to treat chronic liver disease and inflammation [9,10]. Chrysophanol is an anthraquinone derivative isolated from the rhizomes of R. palmatum L. Previous studies demonstrated that chrysophanol shows anticancer, hepatoprotective, neuroprotective, anti-inflammatory, antiulcer, and antimicrobial activities [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Dahuang, the root of Rheum palmatum L ., is a well-known traditional Chinese herbal medicine that has been used to treat chronic liver disease and inflammation [ 9 , 10 ]. Chrysophanol is an anthraquinone derivative isolated from the rhizomes of R. palmatum L .…”
Section: Introductionmentioning
confidence: 99%